2019
DOI: 10.1007/s11060-019-03262-4
|View full text |Cite
|
Sign up to set email alerts
|

Global extracellular vesicle proteomic signature defines U87-MG glioma cell hypoxic status with potential implications for non-invasive diagnostics

Abstract: PurposeGlioblastoma multiforme (GBM) is the most common and lethal of primary malignant brain tumors. Hypoxia constitutes a major determining factor for the poor prognosis of high-grade glioma patients, and is known to contribute to the development of treatment resistance. Therefore, new strategies to comprehensively profile and monitor the hypoxic status of gliomas are of high clinical relevance. Here, we have explored how the proteome of secreted extracellular vesicles (EVs) at the global level may reflect h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 54 publications
2
12
0
Order By: Relevance
“…A more detailed analysis of the involvement of these proteins in the cellular processes is presented in Supplementary Tables S2 and S3 . Similar results for protein functions in glioblastoma exosomes have been described in the literature [ 20 , 21 ]…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…A more detailed analysis of the involvement of these proteins in the cellular processes is presented in Supplementary Tables S2 and S3 . Similar results for protein functions in glioblastoma exosomes have been described in the literature [ 20 , 21 ]…”
Section: Resultssupporting
confidence: 88%
“…A more detailed analysis of the involvement of these proteins in the cellular processes is presented in Supplementary Tables S2 and S3. Similar results for protein functions in glioblastoma exosomes have been described in the literature [20,21] (1433E). Two more proteins, nucleophosmin (NPM) and cofilin (COF1), are present in four exosome samples ( Supplementary Table S1).…”
Section: Proteome Profiling Of Glioblastoma-derived Extracellular Vessupporting
confidence: 89%
“…Indira Chandran et al. (2019)) utilized proteomics and analysed hypo‐ and normo‐EVs from glioblastoma cells and confirmed the increased release of IGFBP3 and CA9 in hypoxia. They showed enrichment of HIF signalling pathway proteins in hypo‐EVs and also validated this altered release at the transcriptional level.…”
Section: Other Rnas and Proteins In Hypoxic Evsmentioning
confidence: 89%
“…It is now clear that GBMs are able to release EVs [ 14 ], thanks to studies that have identified many of the intracellular molecules secreted by EVs. Investigation has been mostly performed on EVs deriving from different human glioma cell lines [ 15 , 16 ] and, also, in GSCs [ 17 , 18 , 19 ] or plasma from patients with primary GBM [ 20 ]. However, it has been limited to isolation and characterization of Exos.…”
Section: Introductionmentioning
confidence: 99%